2014
DOI: 10.1093/glycob/cwt163
|View full text |Cite
|
Sign up to set email alerts
|

Both isoforms of human UDP-glucose:glycoprotein glucosyltransferase are enzymatically active

Abstract: Being recognized as an important constituent of the glycoprotein folding cycle, uridine diphosphate-glucose:glycoprotein glucosyltransferase (UGGT) has been a subject of intense study. Up to now, it is two isoforms, UGGT1 and 2 have been identified, which share ∼ 50% amino acid identity. UGGT1 is a well-documented enzyme which functions as a folding sensor in the endoplasmic reticulum, by the virtue of its ability to transfer a glucose residue to non-glucosylated high-mannose-type glycans of immature glycoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 34 publications
1
52
0
Order By: Relevance
“…It was originally proposed that UGT2 lacks re-glucosylation activity (131) yet, a recent study showed that UGT2 has re-glucosylation activity and similar specificity to UGT1. This study used a cell free re-glucosylation assay (132). Further investigations are required to confirm the function of UGT2.…”
Section: Role Of Ugt1 As a Folding Sensormentioning
confidence: 99%
“…It was originally proposed that UGT2 lacks re-glucosylation activity (131) yet, a recent study showed that UGT2 has re-glucosylation activity and similar specificity to UGT1. This study used a cell free re-glucosylation assay (132). Further investigations are required to confirm the function of UGT2.…”
Section: Role Of Ugt1 As a Folding Sensormentioning
confidence: 99%
“…The plasmids were transfected into 293T cells using Lipofectamine 2000 (Life Technologies Japan, Tokyo, Japan) according to the manufacturer's instructions. After 48 h, the cells were harvested and the recombinant proteins were purified using Anti-FLAG M2-agarose (SigmaeAldrich Japan, Tokyo, Japan) as described previously [22].…”
Section: Expression Of Recombinant Uggt1 In Human Embryonic Kidney (Hmentioning
confidence: 99%
“…It is a large monomeric protein of more than 1500 residues and found in almost all eukaryotes. The activity of UGGT has been probed using native and misfolded glycoproteins (7, 10 -13), glycopeptides (14 -16), and small synthetic substrates (17)(18)(19)(20)(21)(22). These studies have shown a strong selectivity for glucosylation of misfolded over folded substrates.…”
mentioning
confidence: 99%